PERAN PENGELOLA RUMAH BACA DALAM MENINGKATKAN MINAT BACA PADA SISWA SEKOLAH DASAR DI KOTA PONTIANAK - Mauizatul Hasanah; Imran Imran; Fatmawati Fatmawati (ICoTE Proceedings, 2019)
The title of this study is "The Role of Reading House Managers in Increasing Reading Interest in Elementary School Students in Pontianak City". The purpose of this study was to determine the role of Reading House managers in organizing activities to increase reading interest in elementary school students at Rumah Baca, efforts made by the Reading House manager to increase reading interest in elementary school students at Rumah Baca and the obstacles faced by Rumah Baca managers in increasing interest read elementary students at Pontianak Reading House. The approach used is a qualitative approach with descriptive methods. Data collection techniques used were interview techniques and documentation, with data collection tools in the form of interview guides and documentation. Based on the results of interviews and documentation that researchers have carried out proves that the manager's role influences students' reading interest in the Reading House. There are supporting factors, namely the existence of educational institutions as a place of fostering and inhibiting factors, namely the scarcity of the existence of interesting books. The effort taken is to find the cause of the low interest in reading.